Solution-Based Chemical Process for Synthesis of Highly Active Li2S/Carbon Nanocomposite for Lithium-Sulfur Batteries - Strubel, Patrick; Althues, Holger; Kaskel, Stefan (ChemNanoMat, 2016)
A novel method for the preparation of Li2S integrated into porous carbon black as host material by using a facile solution-based chemical process is described. Li2S was synthesized by disproportionation of a Li2S6 polysulfide solution. The combination of a homogeneous Li2S distribution with small Li2S particle size and good contact with the carbon surface leads to ideal properties for the application in high-energy-density long-cycle-life lithium-sulfur batteries. An initial discharge capacity of 1259 mA h g−1 sulfur with good cycle stability as well as low polarization are achieved, rendering the novel method particularly suitable for application in full cells with silicon- or carbon-based anodes, which are used to overcome the main limitations observed using metallic lithium as anode in lithium-sulfur batteries.
CRIS-Team Scopus Importer:2023-03-20
Keywords: batteries; carbon; lithium sulfide; mesoporous materials